Game On - Exploring Gamification in Online Surveys - Eriksson,Karl; Martin Macarro,Rafael; Nerius,Samuel (2025)
This thesis explores how gamification affects respondent engagement and data quality in online surveys. A between-subjects experiment with 203 participants compared a gamified survey featuring progress bars, rewards, feedback, and a storyline with a non-gamified version. The study was guided by the Technology Acceptance Model 2, Self-Determination Theory, and Flow Theory. Results showed that gamification significantly increased time on survey and the average word count per question, suggesting higher cognitive involvement. However, no significant differences were found in completion rates or item non-response rates. These findings indicate that while gamification can improve certain engagement metrics, it does not universally enhance data quality. The study offers practical insights for survey design and highlights directions for future research.
Keywords: Gamification; Online Surveys; Respondent Engagement; Data Quality